Go, building web applications : build real-world, production-ready solutions by harnessing the powerful features of Go : a course in three modules. - Kozyra, Nathan; Ryer, Mat (Learning path., 2016)
Build real-world, production-ready solutions by harnessing the powerful features of Go About This Book An easy-to-follow guide that provides everything a developer needs to know to build end-to-end web applications in Go Write interesting and clever, but simple code, and learn skills and techniques that are directly transferable to your own projects A practical approach to utilize application scaffolding to design highly scalable programs that are deeply rooted in go routines and channels Who This Book Is For This book is intended for developers who are new to Go, but have previous experience of building web applications and APIs. What You Will Learn Build a fully featured REST API to enable client-side single page apps Utilize TLS to build reliable and secure sites Learn to apply the nuances of the Go language to implement a wide range of start-up quality projects Create websites and data services capable of massive scale using Go's net/http package, exploring RESTful patterns as well as low-latency WebSocket APIs Interact with a variety of remote web services to consume capabilities ranging from authentication and authorization to a fully functioning thesaurus Explore the core syntaxes and language features that enable concurrency in Go Understand when and where to use concurrency to keep data consistent and applications non-blocking, responsive, and reliable Utilize advanced concurrency patterns and best practices to stay low-level without compromising the simplicity of Go itself In Detail Go is an open source programming language that makes it easy to build simple, reliable, and efficient software. It is a statically typed language with syntax loosely derived from that of C, adding garbage collection, type safety, some dynamic-typing capabilities, additional built-in types such as variable-length arrays and key-value maps, and a large standard library. This course starts with a walkthrough of the topics most critical to anyone building a new web application. Whether it's keeping your application secure, connecting to your database, enabling token-based authentication, or utilizing logic-less templates, this course has you covered. Scale, performance, and high availability lie at the heart of the projects, and the lessons learned throughout this course will arm you with everything you need to build world-class solutions. It will also take you through the history of concurrency, how Go utilizes it, how Go differs from other languages, and th...